Effects of different solvent and extraction methods on phytosterols and antioxidant activity of cocoa butter and application of cocoa butter in salad dressing - Mohamad, Roiaini (2015)
The addition of phytosterols and antioxidant into food product may give additional health benefit towards consumers. Their stability in a food product may also decrease as the storage increase. Therefore, the objectives of this study were: i) to screen the most suitable solvent for extraction of CB using Soxhlet extraction and ii) to optimize the most suitable extraction methods in producing high amounts of phytosterols and antioxidant activity, iii) to formulate CB based salad dressing (CBSD) and iv) to determine the stability of phytosterols, antioxidant activity and physicochemical properties of CBSD during storage. Dried cocoa beans was treated with four different types of solvents: Hexane (HE), Petroleum ether (PE), Isopropanol (PR) and Ethanol (ET) using Soxhlet extraction. Then, the selected solvent was applied in four different extraction methods: Soxhlet extraction (SE), Ultrasonic extraction (USE), Supercritical extraction CO2 (SCO2) and Supercritical extraction CO2 with Ethanol (SCO2-Ethanol). The CB extracted from selected extraction method was applied in salad dressing formulation with different ratios of cocoa butter (CB) and soybean oil (SB). The selected ratio of CB and SB (30:70) was studied for their stability during 28 days storage at two different temperatures. The yield of CB produced from ET (14.25%) was significantly the lowest than HE and PE (43.24% and 39.31% respectively). ET had significantly (p0.05) similar characteristics (shear stress to shear rate, oscillating sweep stress and emulsion stability test) with CBSD containing 30% CB compared to other ratios. Thus, 30% CBSD with the most stable emulsion was selected for storage study at 4 and 30˚C. However, the physicochemical characteristic, the amount of phytosterols, DPPH assay and TPC of 30% CBSD during storage were decreased with time (from 0 day to 28 days) and increased with temperature suspected due to oxidation of the oil. Thus, the most desirable storage temperature for salad dressing was at 4˚C compared to 30˚C.An excellent stability of 30% CBSD at different temperatures for 28 days offers high potential application in food industries to produce CB based salad dressing enriched with phytosterols and antioxidants. Therefore, the selection of the solvent and the extraction method of cocoa beans is very crucial and may be applicable for the cocoa industry to broaden the application of CB as emulsion products.